Big five personality traits and income - Rejthar, Jan (2018)
This bachelor thesis aims at inspection of the hypothesis: “Personality effects income.”An OLS regression model is used to analyze the hypothesis. The Big Five personality traitsmodel is employed as the taxonomy of personality and translated version of the IPIP 50questionnaire is utilized for assessment of personality of individuals, showing high level ofreliability. Results of the regression analysis are in favor of the hypothesis, becauseagreeableness shows negative and statistically significant effect. Secondary analysis of thedataset of the thesis show differences in personality between sexes in the cases of agreeablenessand neuroticism, both benefiting women, while analysis of the dataset fromopenpsychometrics.org shows differences in all five dimensions. Analysis of the influence ofpersonality on education is inconclusive.